2011
DOI: 10.1074/jbc.m110.185991
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Genomic Response to Dietary Isocaloric Protein Restriction in the Rat

Abstract: We have examined hepatic, genomic, and metabolic responses to dietary protein restriction in the non-pregnant Sprague-Dawley rat. Animals were pair-fed either a 6 or 24% casein-based diet for 7-10 days. At the end of the dietary period, a microarray analysis of the liver was performed, followed by validation of the genes of interest. The rates of appearance of phenylalanine, methionine, serine, and glucose and the contribution of pyruvate to serine and glucose were quantified using tracer methods. Plasma and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
58
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 62 publications
9
58
1
2
Order By: Relevance
“…The underlying reason for this differential regulation remains unclear, but it seems likely that hepatic metabolism is uniquely different in settings of protein versus energy restriction. For instance, our data are consistent with previous work (33) demonstrating that protein restriction triggers adaptive increases in hepatic amino acid synthesis and decreases in hepatic amino Figure 4. LP-induced increases in circulating FGF21 depend on both GCN2 and PPARα signaling.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The underlying reason for this differential regulation remains unclear, but it seems likely that hepatic metabolism is uniquely different in settings of protein versus energy restriction. For instance, our data are consistent with previous work (33) demonstrating that protein restriction triggers adaptive increases in hepatic amino acid synthesis and decreases in hepatic amino Figure 4. LP-induced increases in circulating FGF21 depend on both GCN2 and PPARα signaling.…”
Section: Discussionsupporting
confidence: 82%
“…Although there was no effect of diet on final body weight or body weight gain, 14 days of LP diet increased body adiposity (control: 18.2% ± 0.005%; LP: 20.3% ± 0.008% fat, P = 0.034). Consistent with a state of dietary protein restriction (33), LP diet altered circulating amino acid concentrations, reduced hepatic leucine oxidation, Enhanced fibroblast growth factor 21 (FGF21) production and circulation has been linked to the metabolic adaptation to starvation. Here, we demonstrated that hepatic FGF21 expression is induced by dietary protein restriction, but not energy restriction.…”
Section: Fgf21 Is Rapidly and Robustly Induced By Dietary Protein Resmentioning
confidence: 90%
“…Это также сопровождается нарушением связей в системе гипофиз -гипоталамус -кора надпочечников, что способствует изменению активности ренин-ангиотензи-новой системы, концентрации циркулирующих катехолами-нов и плотности адренорецепторов в тканях [12,28]. Более того, у небеременных крыс изокалорическое ограничение белка в диете приводит к изменению экспрессии генов, связанных с клеточной дифференциацией, транспортом и метаболическими процессами в печени [29]. Эти наблю-дения указывают на важность преконцепционного програм-мирования, доказанного на крысах.…”
Section: влияние недостаточного потребления белкаunclassified
“…Эти наблю-дения указывают на важность преконцепционного програм-мирования, доказанного на крысах. Существуют данные, что изокалорическое ограничение поступления белка к матери может повлиять на синтез серина, который также является важным источником поступления метильных групп in vivo [29]. Пока не ясно, могут ли новорожденные отвечать подоб-ным образом на ограничение поступления белка.…”
Section: влияние недостаточного потребления белкаunclassified
“…These include imbalances in plasma and brain amino acid concentrations in rats [15][16][17] , modulation of energy sensors in the hypothalamus and anterior piriform cortex in rats 18 , and increased activity in the reward areas such as the orbitofrontal cortex and striatum in humans 11 . Low protein diets also enhance energy expenditure in rodents 17,[19][20][21][22] , however, the underlying mechanisms are poorly understood.…”
mentioning
confidence: 99%